2013
DOI: 10.1109/ted.2013.2279892
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxide Trap Density and Profiles of 1-nm EOT Metal-Gate Last CMOS Transistors Assessed by Low-Frequency Noise

Abstract: The low-frequency noise behavior of replacement metal gate high-k/metal-gate MOSFETs with an equivalent oxide thickness of the SiO 2 /HfO 2 bilayer in the range ∼1 nm has been investigated. It will be shown that both the average trap density and its profile derived from the frequency exponent γ of the flicker noise spectra are mainly determined by the interfacial layer (IL) oxide processing, with a higher trap density corresponding with a thinner chemical oxide, compared with a ≤1-nm thermal SiO 2 IL. The thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 44 publications
(62 reference statements)
3
34
0
Order By: Relevance
“…In the case where a pronounced trap density profile is present, one should investigate the whole frequency range in more detail, as already discussed elsewhere. 12,13 Assuming elastic tunneling, the frequency axis of a noise spectrum can be converted into a tunneling depth, using:…”
Section: Discussionmentioning
confidence: 99%
“…In the case where a pronounced trap density profile is present, one should investigate the whole frequency range in more detail, as already discussed elsewhere. 12,13 Assuming elastic tunneling, the frequency axis of a noise spectrum can be converted into a tunneling depth, using:…”
Section: Discussionmentioning
confidence: 99%
“…4e we compare the typical D ot extracted for our BPFETs with literature values for different technologies. [33][34][35][36][37][38][39][40] At room temperature the density of active oxide traps in our devices is~10 17 cm…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the thickness of the IL layer has a high impact on the level of LFN [1] [4] [10]. In this paper we evaluate the low-frequency noise (LFN) in devices with TmSiO IL EOT of 0.3 nm and compare to state-of-the art LFN in published SiO x /HfO 2 devices.…”
Section: Introductionmentioning
confidence: 99%